The Potential of Bajakah Endophytic Fungus (Spatholobus littoralis Hassk) Against Staphylococcus aureus Bacteria - Putri Nadila Utami; Kunti Nastiti; Melviani Melviani; Dede Mahdiyah (International Journal Of Health Science, 2025)
A plant that has great potential as a source of traditional medicine is Spatholobus littoralis Hassk, or better known as bajakah. The research aims to analyze the Potential of Bajakah Endophytic Fungi (Spatholobus littoralis Hassk) Against Staphylococcus aureus Bacteria. This research was conducted at the Pharmaceutical Microbiology Laboratory, Faculty of Health, Sari Mulia University, Banjarmasin. The study used endophytic fungi on Bajakah wood (Spatholobus littoralis Hassk). The research design used was a True Experimental design with the aim of identifying the antibacterial activity of Bajakah endophytic fungi (Spatholobus littoralis Hassk) and testing the inhibitory power of Bajakah endophytic fungi (Spatholobus littoralis Hassk) against Staphylococcus aureus bacteria. Three isolates of endophytic fungi from Bajakah stems (Spatholobus littoralis Hassk) showed antibacterial activity against Staphylococcus aureus bacteria with varying levels of potency. Isolate (JEB 1) which is estimated to originate from Aspergillus sp showed very strong antibacterial activity with an inhibition zone diameter of 27.18 ± 0.725 mm. Isolate (JEB 1) has a Minimum Inhibitory Concentration (MIC) value at a concentration of 5 x 106 ppm and the best Minimum Bactericidal Concentration (MBC) at a concentration of 5 x 106 ppm. These findings indicate that endophytic fungi, especially from Aspergillus sp, have potential as natural antibacterial agents that can be further developed as candidates for new antibacterial materials based on local natural resources.